Analysis of the Influence of Higgs Domino Island Online Games on Adolescent Aggressive Behavior in Labuhanbatu - Gadang Alamanda; Elida Florentina Sinaga Simanjorang; Junita Lubis (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This study aims to determine the impact of the Higgs Domino Island online game on adolescent violent behavior in the Labuhanbatu Regency. Some people in the research area have to spend a significant amount of time in a particular setting as part of this kind of field study, which has a qualitative descriptive approach. This study used 12 informants consisting of 8 adolescents aged between 15 to 17 years and 8 adults aged between 18 to 22 years. In addition, the four mothers’ parents who agreed to take part in the study were parents of children who often played Higgs Domino games online and displays violent behavior. The research results show that the Higgs Domino online game has a relationship with the aggressive behavior of adolescents. Based on the interview results, the authors can analyze that the impact of online games greatly influences the aggressive behavior of teenagers where the child is more emotional and performs actions, such as lying and stealing.